Human cloning religious responses - Cole-Turner, Ronald (Louisville, KN Westminster/John Knox, 1997)
Includes bibliographical references.
Keywords: Cloning -- religious aspects -- Christianity; Cloning -- moral and ethical aspects; Human genetics -- religious aspects -- Christianity; Human genetics -- moral and ethical aspects